The influence of leaders’ promotion of sensemaking on team metacognitions, adaptation and performance: a mediation model - Galante, Ricardo Manuel Ramos (2020)
In today’s competitive and highly dynamic organizational context, it is vital to understand what factors contribute to high levels of performance in teams. In this dissertation, team adaptation and metacognition are analysed as mediators of the relationship between the leaders’ promotion of sensemaking and team performance. A total of 55 teams in audit and consulting services answered two questionnaires, one for leaders and one for members to verify the previously formulated hypothesis. Results show positive effects, supporting the hypothesis that team adaptation and metacognition mediate the relationship between the leaders’ promotion of sensemaking and team performance. Further research should consider a higher number of teams inserted in more diverse settings, to identify if the results are equally strong and applicable to other industries and different contexts.